Calculation and validation of a grain boundary complexion diagram for Bi-doped Ni. (15th March 2017) - Zhou, Naixie; Yu, Zhiyang; Zhang, Yuanyao; Harmer, Martin P.; Luo, Jian
Abstract: A grain boundary (GB) "phase" (complexion) diagram is computed via a lattice type statistical thermodynamic model for the average general GBs in Bi-doped Ni. The predictions are calibrated with previously-reported density functional theory calculations and further validated by experiments, including both new and old aberration-corrected scanning transmission electron microscopy characterization results as well as prior Auger electron spectroscopy measurements. This work supports a major scientific goal of developing GB complexion diagrams as an extension to bulk phase diagrams and a useful materials science tool. Graphical abstract: Highlights: A grain boundary complexion (phase) diagram is computed for Ni-Bi. Predictions have been verified by experiments. Complexion diagrams are an extension to bulk phase diagrams.